The histological and chemical changes occured through the preparation stages of the pastrami produced by using automatic injection and press-machines - Mine Balıkçıer; Şahsene Anar; Hatice Erdost (Eurasian Journal of Veterinary Sciences)
In this study, the histological and chemical changes occured during the production stages of the pastrami produced by using automatic injection and press-machines were investigated. When compared with the muscle sections from the meal before the production stages, the muscle fibres were swollen, endomysium was indefinite after brine injection, endomysium again became evident and the directions of the muscle fibres changed in the same primary bundles after the first and second pressing process, the muscle fibres became swollen again after covered with cemen paste. In the meat stage glycosaminoglicans accumulated in a few cells, but they disappeared after this stage. The observations on the sections, those were prepared from the pastrami sections taken at the end of each stage showed that no changes occured in the content and structure of lipid deposits. The muscle fibres were grouped as thin, medium and thick groups according to their diameters. The diameters ol the thick and medium type of muscle fibres were increased after brine injection and cemen treatment, whereas a siight decrease in the diameters was seen after massaging and first and second pressing and drying stages; the diameters of the thin type ol muscte fibres increased after massaging stage and decreased thereafter. The results of the chemical analyses of the samples taken during different stages of the pastrami production showed thai relative moisture and pH decreased, whereas sattness increased. The pastramies ready to marketing were chemically found to be convenient to the Food Regulation and Standards on the account of chemical analysis.